Analisis Pengaruh Reward terhadap Keaktifan Belajar Siswa Kelas V SDN Panggungrejo 4 - Dwi Karina Rahmawati; Dea Devayanti; Muhammad Fandi Nurhafi; Rika Mellyaning Khoiriya; Endah Novitiani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The low level of student learning engagement in elementary schools has prompted teachers to implement rewards as a form of positive reinforcement. This study aims to describe the reward model implemented by fifth-grade teachers at Panggungrejo 4 Elementary School, its impact on student learning engagement, and the supporting and inhibiting factors. A descriptive qualitative approach was used with semi-structured interviews with one teacher and four students selected through purposive sampling. Data were analyzed using the Miles, Huberman, and Saldana interactive model with thematic coding, resulting in five themes: reward type, delivery mechanism, student response, engagement indicators, and the risk of dependency. The results show that teachers implement physical rewards (stationery and snacks) and a star system as delayed rewards. Their implementation consistently increases the courage to ask questions, participate in discussions, and the courage to speak in front of the class. The findings are supported by Skinner's operant conditioning theory and Piaget's concrete operational stage. Supporting factors include consistency, transparency of criteria, and reward variation; inhibiting factors include reward dependency, uneven distribution, and the temporary nature of engagement. This study concludes that rewards have a positive impact on learning engagement, but must be designed systematically with a gradual fading strategy to foster sustainable intrinsic motivation.